Interventions to reduce porcine epidemic diarrhea virus prevalence in feed in a Chinese swine production system: A case study. Issue 1 (8th July 2021) - Wu, Fangzhou; Cochrane, Roger; Yaros, Joseph; Zhang, Caixia; Tsai, Shih‐Yi; Spronk, Gordon
Abstract: Research has shown that feed and feed ingredients can be one of the potential routes of transmitting viral pathogens into swine farms. In this short communication, we report two cases of Porcine Epidemic Diarrhea (PED) in two sow farms located in eastern China. Immediately after the outbreaks, extensive sampling and testing for genetic materials of PEDV was carried out on farms, and at the feed mill, in an effort to identify possible sources of infection based on field observations of local area viral spread and interventions already implemented to lower risk of this spread. Samples collected from personnel or supplies entering the farms were inspected and proved as low risk factors. In contrast, feed and feed ingredient samples collected at the on‐farm feed bins, and at the feed mill, tested positive for PEDV RNA. Based on these data, multiple interventions to lower viral spread via feed were implemented including (1) simplification of diet formulation excluding high‐risk ingredients, (2) extension of thermal treatment during pellet conditioning and (3) maximising feed quarantine on farm up to 7 days from feed delivery to consumption. Collectively, these interventions appeared to have a positive effect as the prevalence of PED‐related disease and the number of PEDV‐positive feed or feed ingredient samples decreased considerably following implementation.